2017
DOI: 10.7324/rjc.2017.1011609
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Butanol-Diesel Blends in a Compression Ignition Engineto Reduce Emission

Abstract: In this investigation butanol was added to diesel with known percentages to improve the performance of a diesel engine. To avoid separation, Span 80 emulsifier added to the oxygen enriched fuel with water to get suitable blends. The experiment has been conducted in a four stroke, single cylinder diesel engine having different loads at constant speed were investigated. The oxides of nitrogen, carbon monoxide, and smoke opacity were found to be minimum for D70 (70:29:1) blend compared with the other blends. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…The results obtained are in good agreement with the data in the scientific literature. 4,7,11,[28][29][30][31][32][33][34][35][36]…”
Section: Physicochemical Research Of the Synthesized Catalystsmentioning
confidence: 99%
“…The results obtained are in good agreement with the data in the scientific literature. 4,7,11,[28][29][30][31][32][33][34][35][36]…”
Section: Physicochemical Research Of the Synthesized Catalystsmentioning
confidence: 99%
“…Several studies have been reported on the performance, combustion and emission of diesel -n-butanol blends in CI engines with impressive outcomes [21][22][23][24][25]. A lot more research papers were published on the combustion behaviour of binary and ternary blend mixtures of butanol/biodiesel/ and diesel; and butanol/biodiesel/ and diesel fuels [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%